To the Diamond Mountains: A Hundred-Year Journey through China and Korea - Morris-Suzuki, Tessa (Rowman & Littlefield Publishers, 2010)
This compelling and engaging book takes readers on a unique journey through China and North and South Korea. Tessa Morris-Suzuki travels from Harbin in the north to Busan in the south, and on to the mysterious Diamond Mountains, which lie at the heart of the Korean Peninsula's crisis. As she follows in the footsteps of a remarkable writer, artist, and feminist who traced the route a century ago—in the year when Korea became a Japanese colony—her saga reveals an unseen face of China and the two Koreas: a world of monks, missionaries, and smugglers; of royal tombs and socialist mausoleums; a world where today's ideological confrontations are infused with myth and memory. Northeast Asia is poised at a moment of profound change as the rise of China is transforming the global order and tensions run high on the Korean Peninsula, the last Cold War divide. Probing the deep past of this region, To the Diamond Mountains offers a new and unexpected perspective on its present and future.